Reactions of salicylaldehyde and enolates or their equivalents: versatile synthetic routes to chromane derivatives - Masesane, Ishmael B.; Desta, Zelalem Yibralign (Beilstein Journal of Organic Chemistry, 2012)
The reported methodologies for the synthesis of chromane derivatives through the reaction of salicylaldehyde and enolates are discussed. The enolates and their equivalents involved in the reactions discussed in this article were derived from ketones, nitroalkanes, malononitrile and α,β-unsaturated compounds.
Keywords: acetophenone; chromane; enolates; malononitrile; Michael addition; salicylaldehyde